ANALISIS KINERJA KEUANGAN PT. BPR BANK DAERAH BANGLI (PERSERODA) PERIODE 2017 – 2021 - Ni Putu Juni Asmariati; Fridayana Yudiaatmaja; Ni Made Suci (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to determine the financial performance of PT. BPR Regional Bank Bangli (Perseroda) for the period 2017 to 2021 using the RGEC method and the EVA method. This descriptive research uses a quantitative approach. The results showed that 1) the financial performance of PT BPR Daerah Bangli using the RGEC method with the predicate Very Healthy composite rating 1 (PK 1) complies with the standards set by Bank Indonesia and OJK regulations. 2) the financial performance of PT BPR Regional Bank Bangli using the EVA method is able to provide economic added value of Rp.1,045,513 over the last five years, this means that in 2017-2021 the EVA value is greater than zero, and that means that PT BPR Regional Bank Bangli (Perseroda) gets a positive value and this number has a positive value.By testing statistical analysis, namely using data analysis techniques t-test one sample. This analysis technique is used because the number of sample members (df) = n-1 = 4. and based on the calculations the value < is obtained so that the number shows that Ho is rejected and Ha is accepted. This means that the statistical test that states the level of financial performance of PT BPR Regional Bank Bangli (Perseroda) has been able to create economic value from the expected positive criteria that can be accepted, which means that the management of PT Regional Bank Bangli has succeeded in creating economic added value for the company.